2018
DOI: 10.1007/s10484-018-9426-0
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Neurofeedback Increases Beta ERD During Mental Rotation Task

Abstract: The purpose of the present study was to identify the effect of acoustic neurofeedback on brain activity during consecutive stages of mental rotation of 3D objects. Given the fact that the process of mental rotation of objects is associated with desynchronisation of beta rhythm (beta ERD), it was expected that suppression in this band would be greater in the experimental group than in the controls. Thirty-three participants were randomly allocated to two groups performing the classic Shepard–Metzler mental rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
4
6
0
Order By: Relevance
“…The beta ERD was decreased in the high-altitude group, suggesting that high-altitude immigrants needed a longer response time to complete the mental rotation task, which may be associated with the impaired control function. The beta ERD in the premotor cortex with the increase in rotation angles might be related to using motor strategies during the mental rotation task (Ozga et al, 2018 ). We speculated that using the motor imagination strategy to complete mental rotation task was able to consume more mental resources, and there was a significant difference in beta power between the two groups, which indicated that the high-altitude group needed more cognitive control processing ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beta ERD was decreased in the high-altitude group, suggesting that high-altitude immigrants needed a longer response time to complete the mental rotation task, which may be associated with the impaired control function. The beta ERD in the premotor cortex with the increase in rotation angles might be related to using motor strategies during the mental rotation task (Ozga et al, 2018 ). We speculated that using the motor imagination strategy to complete mental rotation task was able to consume more mental resources, and there was a significant difference in beta power between the two groups, which indicated that the high-altitude group needed more cognitive control processing ability.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the central alpha ERD was correlated with mental rotation processing, in which the alpha ERD was increased with the slower reaction time (Chen et al, 2013 ). Beta ERD was related to the rotation angles at the later stage of the mental rotation task (Ozga et al, 2018 ). As to the parietal region, previous studies have already confirmed that it is a target region to be significantly activated during the mental rotation task (Alivisatos and Petrides, 1997 ; Harris and Miniussi, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid increase in the number of publications concerning Brain-Computer Interfaces (BCI) is observed (Mikołajewska and Mikołajewski, 2012, 2013, 2014; Teruel et al, 2017; Ozga et al, 2018; Wierzgała et al, 2018) and the EEG activity can be recognized as one of possible solutions in BCI engineering (Kotyra and Wojcik, 2017a,b). In addition, any ideas for finding biomarkers of psychiatric disorders (Chapman and Bragdon, 1964; Sutton et al, 1965; Campanella, 2013; Golonka et al, 2017) are in demand as the interview is still the most often used tool in psychiatry to make the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on visual perception indicate that top-down visual attention can be activated in parallel with bottom-up driven object recognition processes, afforded by bidirectional information flow (Noorman et al, 2018 ). Linguistic cues guide interpretation of visual scenes (top-down), while perceptual information shapes interpretation of linguistic input (Vulchanova et al, 2019 ) and acoustic neurofeedback might improve the process of mental rotation of 3D objects (bottom-up) (Ozga et al, 2019 ). The interaction between top-down and bottom-up driven visual and auditory attention again raises questions about the learning styles hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%